2023
DOI: 10.1021/acsomega.3c02962
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dencichine in Panax notoginseng in the Forest and Field Using High Performance Liquid Chromatography

Abstract: Dencichine is a nonprotein amino acid, an effective ingredient in Panax notoginseng with hemostatic and anti-inflammatory effects. There are few studies on the effects of regions and cultivation models on the accumulation of dencichine. In the current study, the content of dencichine in P. notoginseng collected from its global cultivation and trading center Yunnan, China, (>640 samples) was determined using an optimized high-performance liquid chromatography method coupled with a diode array detector but witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This dual promotion led to a much greater increase in nutrient absorption and saponin accumulation per unit area of P. notoginseng (Parent et al 2012). Ji et al (2023) and Wang et al (2023a, b) reported that nutrient uptake and the notoginsenoside content significantly improved in the cultivation of P. notoginseng in pine forests. Similar studies have also shown that the contents of 20 monomeric saponins, such as Rg1 and Re, significantly increased in P. ginseng cultivated in a Pinus sylvestris var.…”
Section: Discussionmentioning
confidence: 96%
“…This dual promotion led to a much greater increase in nutrient absorption and saponin accumulation per unit area of P. notoginseng (Parent et al 2012). Ji et al (2023) and Wang et al (2023a, b) reported that nutrient uptake and the notoginsenoside content significantly improved in the cultivation of P. notoginseng in pine forests. Similar studies have also shown that the contents of 20 monomeric saponins, such as Rg1 and Re, significantly increased in P. ginseng cultivated in a Pinus sylvestris var.…”
Section: Discussionmentioning
confidence: 96%